EFEK ANTIBAKTERI EKSTRAK BUNGA PACING PUTIH (Costus speciosus (J. Koenig) Sm.) TERHADAP BAKTERI Escherichia coli - Ersa Marina Rahmawati; Eva Marliana; Ritbey Ruga (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
This study was conducted with the aim of identifying the antibacterial activity of crude ethanol extract, ethyl acetate fraction, methanol:water fraction and n-hexane fraction of white pacing flower (Costus speciosus (J. Koenig) Sm.). Sample preparation was carried out using the extraction method, namely maceration with 96% ethanol and obtained a crude extract of ethanol and continued by partition by liquid-liquid extraction method and obtained the n-hexane, the ethyl acetate, and the methanol:water fractions. The antibacterial activity test was carried out on the four samples using the well diffusion method with modification against Escherichia coli ATCC 25922. The antibacterial activity test showed activity in the crude extract of ethanol with an inhibition zone diameter of 7.7 mm. Keyword: white pacing, antibacterial, Escherichia coli